Predictive Maintenance for Injection Molding Machines Enabled by Cognitive Analytics for Industry 4.0 - Rousopoulou, Vaia; Nizamis, Alexandros; Vafeiadis, Thanasis; Ioannidis, Dimosthenis; Tzovaras, Dimitrios (Frontiers in Artificial Intelligence, 2020)
The exploitation of big volumes of data in Industry 4.0 and the increasing development of cognitive systems, strongly facilitate the realm of predictive maintenance for real-time decisions and early fault detection in manufacturing and production. Cognitive factories of Industry 4.0 aim to be flexible, adaptive and reliable, in order to derive an efficient production scheme, handle unforeseen conditions, predict failures and aid the decision makers. The nature of the data streams available in industrial sites and the lack of annotated reference data or expert labels, create the challenge to design augmented and combined data analytics solutions. This paper introduces a cognitive analytics, self- and autonomous-learned system bearing predictive maintenance solutions for Industry 4.0. A complete methodology for real-time anomaly detection on industrial data and its application on injection moulding machines are presented in this study. Ensemble prediction models are implemented on the top of supervised and unsupervised learners and build a compound prediction model of historical data utilizing different algorithms’ outputs to a common consensus. The generated models are deployed on a real-time monitoring system, detecting faults in real-time incoming data streams. The key strength of the proposed system is the cognitive mechanism which encompasses a real-time self-retraining functionality based on a novel double oriented evaluation objective, a data-driven and a model-based one. The presented application aims to support maintenance activities from injection moulding machines’ operators and demonstrate the advances that can be offered by exploiting AI capabilities in Industry 4.0.